Post-hoc analysis of single nucleotide polymorphism profile for eyes with vascularized pigment epithelial detachment due to ARMD - Lee, Daniel; Chan, Clement K; Abraham, Prema; Sarraf, David (European journal of ophthalmology, 2021)
This post-hoc case-control study compares single nucleotide polymorphism (SNP) profile of eyes with vascularized pigment epithelial detachment (vPED) due to age-related macular degeneration (ARMD) with: (1) Control-1 eyes (no ARMD and AREDS Severity Scale 0); and (2) Control-2 eyes (drusen or AREDS Severity Scale 2). SNP profile of High Responders (HR) was also compared with Low Responders (LR) to ranibizumab. Blood samples from 40 patients with vPED treated with ranibizumab were sent for SNP-specific genotype analysis for comparison of variant allele frequencies of 23 SNPs associated with ARMD (VAF) to VAF in 184 Control-1 eyes, and VAF in 85 Control-2 eyes. VAF of HR-50 (⩾50% decrease in PED height) and VAF of HR-75 (⩾75% decrease in PED height) were also compared with VAF of LR. These SNPs were more frequent in vPED than Control-1 eyes: APOE rs4420638 (A/G), HTRA1 rs104904924 (G/T), VEGF rs943080 (T/C), CFH rs1061170 (T/C), CFH rs2274700 (C/T), CFH rs10737680 (A/C), CFH rs10801555 (G/A). These SNPs were more frequent in vPED than Control-2 eyes: APOE rs4420638 (A/G), CFI rs4698775 (G/T), COL15A1/TGFBR1 rs334353 (T/G). FRK rs3812111 (T/A) was more frequent in HR-50 and HR-75 eyes compared with LR. Seven SNPs were more frequent in vPED eyes than non-ARMD eyes, and three SNPs were more frequent in vPED eyes than drusen eyes. Adjusting for multiplicity, only CFH rs2274700 (C/T) was significant for first comparison, and only COL15A1/TGFBR1 rs334353 (T/G) was significant for second comparison. APOE rs4420638 (A/G) was the single SNP more frequently linked to vPED eyes for both comparisons. FRK rs3812111 (T/A) was consistently associated with high responders.